Should wages be subsidized in a pandemic? - Brant Abbott; Phan Van Nam (Queen's University, Department of Economics, 2022)
We use a labor search model with heterogenous households and firms to study the efficacy of a wage subsidy during a pandemic, relative to enhancing unemployment benefits. A large proportion of the economy is forced to shut down, and firms in that sector choose whether to lay off workers or keep them on payroll. A wage subsidy encourages firms to keep workers on payroll, which speeds up labor market recovery after the pandemic ends. However, a wage subsidy can be costlier than enhancing unemployment benefits. If the shutdown is long or profit margins are low then a wage subsidy is preferable, and vice-versa. The optimal mixture of policies includes a wage subsidy that covers 90% the first 200/week of earnings, and expands unemployment benefits to cover all salary up to 275/week. Low income workers, as well as those in less productive jobs, benefit the most from a wage subsidy.
Keywords: E2; E32; J40; 330; wage subsidy; unemployment insurance; search; pandemic; Covid-19